Natural disasters and spatial heterogeneity in damages: the birth, life and death of manufacturing plants. (10th November 2017) - Cole, Matthew A; Elliott, Robert J R; Okubo, Toshihiro; Strobl, Eric
Abstract: In this paper, we use the 1995 Kobe earthquake as a natural experiment to examine the impact of a large exogenous physical shock on local economic activity. For the first time we are able to control for local spatial heterogeneity in the damage caused by a natural disaster using geo-coded plant location and unique building-level surveys. In a survival analysis of manufacturing plants, our results show that building-level damage significantly affects a plant's likelihood of failure and this effect persists for up to 7 years. Further analysis demonstrates that the plants most likely to exit as a result of earthquake damage are the least productive which is suggestive of a cleansing effect as the average productivity rate of the remaining plants increases. We also find that continuing plants experience a temporary increase in productivity following the earthquake consistent with a 'build back better' effect. In terms of local regeneration our results indicate that plant births increase in areas with more severe damage consistent with redevelopment plans for Kobe.